2008
DOI: 10.1021/jf073095y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Rooibos (Aspalathus linearis) Aqueous Extract and Antioxidant Yield with Fungal Enzymes

Abstract: The leaves and stems of the Rooibos plant ( Aspalathus linearis) are used for the production of an herbal tea known for its health promoting properties, which have been linked to its flavonoid content but which is substantially reduced by the traditional processing method employed. Selected food-grade fungi were screened for their potential to improve the yield of soluble matter extracted from rooibos plant material. Fungal cocktails of hydrolyzing enzymes enhanced either the yield of soluble solids ( Lentinul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Among the flavonoids, flavonol- O -glycosides can be readily deglycosylated with acidification, juicing, and heat [43] yet with anthocyanidins, acid and acylation of the glucoside stabilize their flavylium cation [266,267,268], as shown in Figure 1. Moreover, C -glycosylations are the most resilient to cleavage by enzymes or food processing; hence these types of flavonoid glycosides are presumed less bioavailable than their O -glycoside forms [264,269,270]. The bioavailability of C -glycosides of apigenin (aspalathin) and luteolin (nothofagin) and four eriodictyol- C -glycoside isomers were investigated using unfermented and fermented leaves of rooibos tea [271].…”
Section: Foods Designed To Enhance Delivery Of Bioactive Flavonoidmentioning
confidence: 99%
“…Among the flavonoids, flavonol- O -glycosides can be readily deglycosylated with acidification, juicing, and heat [43] yet with anthocyanidins, acid and acylation of the glucoside stabilize their flavylium cation [266,267,268], as shown in Figure 1. Moreover, C -glycosylations are the most resilient to cleavage by enzymes or food processing; hence these types of flavonoid glycosides are presumed less bioavailable than their O -glycoside forms [264,269,270]. The bioavailability of C -glycosides of apigenin (aspalathin) and luteolin (nothofagin) and four eriodictyol- C -glycoside isomers were investigated using unfermented and fermented leaves of rooibos tea [271].…”
Section: Foods Designed To Enhance Delivery Of Bioactive Flavonoidmentioning
confidence: 99%
“…These unusual compounds have received a significant deal of attention, not least because of their abundance in this tisane and the importance of this principal South African export to its home economy. Indeed, the routine quantification of both aspalathin (2 ,3,4,4 ,6 -pentahydroxy-3-C--Dglucopyranosyldihydrochalcone) and the 2 ,4,4 ,6 tetrahydroxylated analogue, nothofagin, has become an accepted measure of rooibos quality, with several publications detailing methodologies for analysis and abundance in material from various processing yards and following several processing protocols (Bramati et al, 2003;Bramati et al, 2002;Joubert, 1996;Joubert and deVilliers, 1997;Joubert et al, 2008;Manley et al, 2006;Pengilly et al, 2008;Rabe et al, 1994;Schulz et al, 2003;Standley et al, 2001;vonGadow et al, 1997). The predominant factor determining the concentration of these two C-glycosyl dihydrochalcones in rooibos tea is the 'fermentation' process.…”
Section: IV Edible Leaves and Stemsmentioning
confidence: 99%
“…Previous reports indicated that the soft-rot fungus R. oryzae produce significant levels of laccase, endoglucanase and endoxylanase activity [27], suggesting that it should be able to also produce ferulic acid esterases. the four strains evaluated in this study produced 2 to 3 U/ml Fae in liquid minimal medium with triticale, with A. tubingensis and R. oryzae being able to extract ca.…”
Section: Discussionmentioning
confidence: 99%